The Role of International Trade on Economic Growth in Somalia - Abdi, Abdifatah Mohamed; Qutieshat, Abubaker (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This paper investigated the role of international trade on economic growth in Somalia, the main objective of the paper is to find out the role of export and import on economic growth in Somalia and to determine the relationship between international trade and economic growth in Somalia. Design/methodology/approach: Somalia’s major exports are livestock, bananas, skins, fish, charcoal, and scrap metal, the major export partners included the United Arab Emirates, Yemen, and Oman. The studies in 2020 indicated that Somalia was the number 173 economy in the world in terms of total exports and number 140 in total imports. Findings: In 2021, Somalia exported a total of 482million USD, making it the number 168 exporter in the world, during the last five reported years, the exports of Somalia have changed by 149millionm USD from 631million USD in 2016 to 482million USD in 2021. Furthermore, the economy is described as a very open economy according to the ratio of imports plus exports to GDP which is 91.5 percent, the 7th highest in Sub-Saharan Africa and 45th highest in the world. Practical implications: The major export of Somalia is livestock which is accompanied by its products i.e. hides and skins though the country deliberately depends on imports of food and non-food items. On the contrary, imports start from neighboring countries including Gulf countries, in South East Asia, and Somalia’s exports for 2021 were 1.53B, a %30.05 increase from 2020, Contribution of livestock to the national economy is estimated at %60-65. Paper type: Literature review